2007
DOI: 10.1002/dvdy.21140
|View full text |Cite
|
Sign up to set email alerts
|

Ras signaling modulates activity of the ecdysone receptor EcR during cell migration in the drosophila ovary

Abstract: Ecdysone Receptor (EcR) mediates effects of the hormone ecdysone during larval molts, pupal metamorphosis, and adult female oogenesis. In the ovary, egg chamber formation requires interactions between the somatic follicle cell (FC) epithelium and the germ line nurse cell/oocyte cyst. Previous work has shown EcR is required in the germ line for egg chamber maturation, and here we examine EcR requirements in the FC at late stages of oogenesis. EcR protein is ubiquitous in the FC but its activity is restricted, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 76 publications
7
48
1
Order By: Relevance
“…Because ecdysteroid secretion is mediated through a regulated vesicular trafficking mechanism (42), it is conceivable that follicle cells, nurse cells, or both could produce local pulses of ecdysteroids to promote egg chamber development at each transition during oogenesis. This hypothesis is consistent with the finding that the ligand sensor for ecdysteroids shows a stage-specific activity including stage 10 and stage 14 (32,33). This notion is further supported by this study that up-regulation of Shd in mature follicle cells produces 20E to regulate ovulation and a previous study that local ecdysteroids produced in follicle cells regulate border cell migration (37).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because ecdysteroid secretion is mediated through a regulated vesicular trafficking mechanism (42), it is conceivable that follicle cells, nurse cells, or both could produce local pulses of ecdysteroids to promote egg chamber development at each transition during oogenesis. This hypothesis is consistent with the finding that the ligand sensor for ecdysteroids shows a stage-specific activity including stage 10 and stage 14 (32,33). This notion is further supported by this study that up-regulation of Shd in mature follicle cells produces 20E to regulate ovulation and a previous study that local ecdysteroids produced in follicle cells regulate border cell migration (37).…”
Section: Discussionsupporting
confidence: 92%
“…Ecdysteroids have long been known to play essential roles in developmental transitions, such as larval molting and metamorphosis (27,28). In contrast, the roles of ecdysteroids in adult physiology have just started to emerge (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…Although the in vivo functional significance of USP binding on chorion gene promoters has yet to be investigated, this may be related to a control of the ecdysone signaling on chorion gene expression. Supporting this hypothesis, Hackney et al (2007) have recently shown that the EcR activity regulates chorion gene expression and amplification during eggshell formation.…”
Section: Trans-acting Elementsmentioning
confidence: 81%
“…The development and functioning of follicle cells is known to be regulated by ecdysone (Buszczak et al, 1999;Carney and Bender, 2000;Terashima et al, 2005;Hackney et al, 2007;Sun et al, 2008;Bernardi et al, 2009;Boyle and Berg, 2009;Romani et al, 2009). Having characterized SMRTER as a transcriptional Number of eggs produced by the control, homozygous BG01648, and heterozygous BG01648/PL6 females.…”
Section: Smrter Inhibits Ecdysone Activity In Follicle Cellsmentioning
confidence: 99%